A New Approach to Global Studies from the Perspective of Small Nations. - Date, Kiyonobu. (The University of Tokyo-Routledge Global Studies Series, 2023)
With emphasis on East Asian and North American examples - notably Japan and Quebec - Date, Laniel and their contributors take a new approach to the understanding of small nations and their role in the international system.